Wrażliwość (nie tylko) artystyczna - Szpunar, Magdalena (Kultura i Społeczeństwo, 2017)
This article starts with an analysis of sensitivity, which is a two-sided trait. We value and admire sensitive people, but we may also consider them to be weak individuals, unable to cope. An overly intense reception of the world can sometimes lead to alienation. In today’s computerized, rationalized world, where efficiency matters above all, feelings can be a burden; reflection postpones immediate success. However, academic knowledge and artistic creativity require sensitivity to the world and the individualization of thinking and feeling. In considering philosophical ideas and the findings of researchers of the human mind, the author demonstrates that sharpened sensitivity and being different are essential traits of the creative attitude, while their lack testifies to a society’s regression.